Fourth Five-Year Plan Madras State Draft Outline - Planning Commission (Planning Commission, 1966)
The basic decisions governing the rate of growth, the size and pattern of investment are all taken at the national level. the State Plan should conform broadly to the targets and objectives of the National Plan and assist in their fulfilment. It should also be consistent with the economic and social philosophy underlying the National Plan. But within this frame-work, the Plan of each State should take into consideration its own special economic and social problems, the level of development reached in different sectors and the need for full utilization of its natural and human resources for securing balanced development.
Madras State